(untitled) (Boletin Médico de Postgrado, 2020)
Giant hydronephrosis is considered a rare entity, characterized by the presence of at least 1 liter of fluid within the pielocalicial system; is more frequent in males and often asymptomatic. We present an 85-year-old female patient who has a 6-year complain of left lumbar pain associated with increase in abdominal circumference. On CT scan, a giant left hydronephrotic pouch is evidenced, with a thinned renal wall that does not concentrate or eliminate contrast. We present a 61 year-old male who refers a 5-year asymptomatic increase in abdominal circumference. The CT scan reveals significant dilatation of the kidney and right collecting system secondary to ureteral lithiasis. Both patients undergo simple nephrectomy. The most frequent etiology of giant hydronephrosis is ureteropelvic junction stenosis followed by lithiasic and tumor pathology. It is important to consider this entity as a differential diagnosis in the case of abdominal cystic masses.